Seismic Activity Simulation and Detection of Wenchuan Earthquake Sequence - Zhang, Mosi (Scientific Journal of Technology, 2026)
The Coulomb rate state model (CRS) based on rate state-dependent constitutive law simulates the seismic activity of three main earthquakes in Wenchuan earthquake sequence. The results show that the model considering the trigger source of secondary aftershocks is more in line with the observation. We come to the conclusion that the trigger of the main earthquake sequence is generated by the self-excitation of small earthquakes under the stress field dominated by Coulomb stress of the main earthquakes of adjacent faults, which is similar to the point process model of ETAS.